Infants are sensitive to cultural differences in emotions at 11 months. - Liquan Liu; Mieke du Toit; Gabrielle Weidemann (PLoS ONE, 2021)
A myriad of emotion perception studies has shown infants' ability to discriminate different emotional categories, yet there has been little investigation of infants' perception of cultural differences in emotions. Hence little is known about the extent to which culture-specific emotion information is recognised in the beginning of life. Caucasian Australian infants of 10-12 months participated in a visual-paired comparison task where their preferential looking patterns to three types of infant-directed emotions (anger, happiness, surprise) from two different cultures (Australian, Japanese) were examined. Differences in racial appearances were controlled. Infants exhibited preferential looking to Japanese over Caucasian Australian mothers' angry and surprised expressions, whereas no difference was observed in trials involving East-Asian Australian mothers. In addition, infants preferred Caucasian Australian mothers' happy expressions. These findings suggest that 11-month-olds are sensitive to cultural differences in spontaneous infant-directed emotional expressions when they are combined with a difference in racial appearance.